Evaluation of Egyptian bentonite and nano-bentonite as drilling mud - M.I. Abdou; A.M. Al-sabagh; M.M. Dardir (Egyptian Journal of Petroleum)
Nano-particles of bentonite have been prepared by nano-grinding. The nano-bentonite was characterized by X-ray fluorescence analysis (XRF), X-ray powder diffraction (XRD), thermal gravimetric analysis (TGA) and Transmission electron microscopy (TEM). The bentonite particles had been ground to the size ranging from 4 to 9 nm. Both natural and nano-bentonite were evaluated as drilling mud. The evaluation involved the study of the rheological properties, filtration and gel strength before and after treatment with viscosities and filter loss agent, and compared with the American Petroleum Institute API bentonite. With decreasing the grain size of bentonite to the nano-scale, the results were not satisfied to the API -standard.